2012
DOI: 10.1007/s40261-012-0029-x
|View full text |Cite|
|
Sign up to set email alerts
|

Bioequivalence and Tolerability Assessment of a Novel Intravenous Ciclosporin Lipid Emulsion Compared to Branded Ciclosporin in Cremophor® EL

Abstract: BackgroundCiclosporin is used as an immunosuppressant in current clinical practice but recent research implies novel indications for the drug, such as neuro- and cardioprotection. The intravenous formulation currently on the market, Sandimmune® Injection (Sandimmune®), uses Cremophor® EL as emulsifying excipient. Cremophor® EL is known to cause hypersensitivity reactions in some patients, ranging from skin reactions to potentially fatal anaphylactic shock.ObjectivesThe primary objective was to assess if CicloM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 53 publications
1
15
1
Order By: Relevance
“…The investigational product was a lipid emulsion formulation of cyclosporine (CicloMulsion, NeuroVive Pharmaceutical), 13 administered intravenously at a dose of 2.5 mg per kilogram of body weight. The control group received a matching placebo formulation.…”
Section: Study Populationmentioning
confidence: 99%
“…The investigational product was a lipid emulsion formulation of cyclosporine (CicloMulsion, NeuroVive Pharmaceutical), 13 administered intravenously at a dose of 2.5 mg per kilogram of body weight. The control group received a matching placebo formulation.…”
Section: Study Populationmentioning
confidence: 99%
“…However, the recently published CYCLE study, which used the Sandimmune formulation, failed to show a significant difference in primary endpoint (resolution of ST-segment ≥ 70%) [20]. The CicloMulsion preparation has been found to have similar pharmacokinetics and rather fewer adverse effects compared to Sandimmune preparation [25]. A study done on patients undergoing coronary artery bypass grafting surgery found no significant difference between the peak troponin T in CsA and placebo groups, except for the high-risk group with prolonged surgery -it showed that the extent of perioperative myocardial infarction was reduced in high-risk CsA patients [26].…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown bioequivalence between cyclosporine formulations in humans. 54 Piglets were randomized to 20 mg/kg/day (i.v.) of either the NeuroSTAT or Sandimmune formulation of cyclosporine ( N = 3/group).…”
Section: Methodsmentioning
confidence: 99%
“…NeuroSTAT ® is a novel lipid emulsion containing cyclosporine that differs from the Sandimmune formulation, which contains the solubilizer, Kolliphor EL (previously named Cremophor EL), which is known to cause hypersensitivity reactions in some patients, ranging from skin reactions to potentially fatal anaphylactic shock. 54 Further, a secondary aim was to perform a systematic pharmacokinetics (PK) evaluation in order to create a bridge between the existing pre-clinical studies, primarily in rodents, and human clinical trials for TBI.…”
Section: Introductionmentioning
confidence: 99%